Divorce and its effects on women rights - A field study in Baghdad city / ALMADAIN COURT (Journal of the College of Education for Women, 2019)
The problem of divorce from the phenomena that characterized the nature of privacy,although their impact beyond the individual to include the community as a whole, the partiesto the relationship affected by divorce caused them harm moral and material for a long time,resulting imbalance in the personal relationship and family and social relations because of thehigh divorce rates, particularly in Iraq high rates of 28690 thousand cases in 2004 to 59 515thousand cases in 2011 and an increase of more than (100%) during the period above, and thisrise caused by aggravation of many of the problems led the reasons for social, economic andincompatibility spouses, health and lack of reproduction, not spending The wife and children,to marry at an early age, violence against the wife, to marry a second wife, the abandonmentof the husband to the wife, treason and others, and is an indicator may reflect a deteriorationin the quality of social life.